CHAMPIONSHUB - Fernandes, Pedro Felipe De Souza; Fonseca, Ana Karen Soares; Oliveira, João Victor Nascimento; de Lima, Henrique Valle; Alcântara, Júlia Botelho de (CIPEEX, 2024)
ELECTRONIC GAMES STAND AS ONE OF THE MOST POPULAR FORMS OF GLOBAL ENTERTAINMENT, CAPTIVATING MILLIONS OF PLAYERS. IN BRAZIL, IN PARTICULAR, ELECTRONIC GAMES HAVE GARNERED A SUBSTANTIAL AND DEVOTED FAN BASE ACROSS VARIOUS PLATFORMS. AMONG THE MYRIAD GAME MODES, COMPETITIVE GAMING EMERGES AS A DOMINANT FORCE, PITTING PLAYERS AGAINST EACH OTHER IN THRILLING PLAYER-VERSUS-PLAYER CONTESTS TO DETERMINE THE VICTOR. BUILDING UPON THIS FOUNDATION, TOURNAMENTS AND PROFESSIONAL MATCHES HAVE BEEN ESTABLISHED WITH THE EXPLICIT GOAL OF ELEVATING THE LEVEL AND EXCITEMENT OF THE COMPETITION. HENCE, THE CORE OBJECTIVE OF THIS PROJECT IS TO PROPOSE THE DEVELOPMENT OF AN ELECTRONIC SPORTS TOURNAMENT MANAGEMENT SYSTEM. IN THIS ENDEAVOR, THE BACK-END DEVELOPMENT WILL HARNESS THE PROWESS OF KOTLIN AND JAVA, TAPPING INTO THEIR ROBUST AND PROVEN CAPABILITIES FOR HANDLING THE SYSTEM’S DATA MANAGEMENT, SERVER-SIDE LOGIC, AND DATABASE INTERACTIONS. SIMULTANEOUSLY, THE FRONT-END WILL BE METICULOUSLY CRAFTED USING FLUTTER, A VERSATILE AND EFFICIENT FRAMEWORK CELEBRATED FOR ITS CAPACITY TO CREATE NATIVELY COMPILED APPLICATIONS FOR MOBILE, WEB, AND DESKTOP FROM A SINGLE CODEBASE. FLUTTER’S ADAPTABILITY AND STREAMLINED USER INTERFACE DEVELOPMENT WILL PLAY A PIVOTAL ROLE IN ENSURING AN EXCEPTIONAL USER EXPERIENCE FOR ALL PARTICIPANTS IN GAMING TOURNAMENTS. THE SYSTEM’S OVERARCHING AIM IS TO PROVIDE PLAYERS WITH A USER-FRIENDLY AND EFFICIENT EXPERIENCE, ASSISTING THEM IN ORGANIZING AND PARTICIPATING IN COMPETITIONS. TO ACHIEVE THIS GOAL, AN ARRAY OF SYSTEM DEVELOPMENT METHODOLOGIES WILL BE ADOPTED, ENCOMPASSING EXPLORATORY AND LITERATURE RESEARCH, AND THE UTILIZATION OF AGILE TOOLS, TECHNIQUES, AND METHODOLOGIES. THE PROJECT’S OBJECTIVES INCLUDE THE IMPLEMENTATION OF A MINIMUM VIABLE PRODUCT (MVP), THE METICULOUS IDENTIFICATION OF SPECIFIC DEMANDS AND REQUIREMENTS THROUGH EXTENSIVE STAKEHOLDER ENGAGEMENT, AND A RELENTLESS COMMITMENT TO ENHANCING THE OVERALL USER EXPERIENCE. CONSEQUENTLY, THE EXPECTATION IS TO HAVE A POSITIVE IMPACT ON THE USER GROUPS UTILIZING THE SYSTEM, MAKING IT STRAIGHTFORWARD FOR ANY USER TO CREATE OR JOIN A TOURNAMENT QUICKLY AND INTUITIVELY.